Penyuluhan Bahaya Perilaku Seks Pranikah Pada Remaja Di Pondok Pesantren Al-Imdad Kab. Bantul - Izhara, Fatimah; Purwanti, Eka; Marera, Gantari Inggit; Latar, Nurfika; Putri , Silvia Rizki Syah; Fatimatasari; Ayuningrum, Lia Dian (Jurnal Pengabdian Masyarakat (JUDIMAS), 2025)
Sexual behavior can be defined as a form of behavior driven by sexual desire either with the opposite sex or the same sex. Premarital sex is basically a sexual activity carried out by individuals with other people before marriage. Lack of adolescent knowledge of reproductive knowledge also occurs due to the influence of social media which provides inaccurate and incorrect information is one of the causes. The impact of problems arising from lack of knowledge of reproductive health is Unwanted Pregnancy (KTD), abortion, and early marriage, STIs or STDs and HIV / AIDS. This community service activity aims to increase adolescent knowledge about premarital sex and its impacts and prevention efforts for adolescent girls at the Al-Imdad Islamic Boarding School, Pajangan District, Bantul Regency. The method of this activity includes planning, programming, implementation, socialization and evaluation. The results of this activity show that there is an increase in adolescent knowledge about the dangers of premarital sexual behavior by giving quizzes before and after being given material to measure their level of knowledge.